2013
DOI: 10.1093/jxb/ert261
|View full text |Cite
|
Sign up to set email alerts
|

Application of HB17, an Arabidopsis class II homeodomain-leucine zipper transcription factor, to regulate chloroplast number and photosynthetic capacity

Abstract: Transcription factors are proposed as suitable targets for the control of traits such as yield or food quality in plants. This study reports the results of a functional genomics research effort that identified ATHB17, a transcription factor from the homeodomain-leucine zipper class II family, as a novel target for the enhancement of photosynthetic capacity. It was shown that ATHB17 is expressed natively in the root quiescent centre (QC) from Arabidopsis embryos and seedlings. Analysis of the functional composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
1
15
1
Order By: Relevance
“…Under normal conditions, we found that ATHB17 was primarily expressed in the root, with weak expression in the shoot, consistent with the previous report36. However, Hymus et al 34. only detected very weak ATHB17 signal in specific cells in the embryonic, QC area of primary and lateral roots, through in situ hybridization analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Under normal conditions, we found that ATHB17 was primarily expressed in the root, with weak expression in the shoot, consistent with the previous report36. However, Hymus et al 34. only detected very weak ATHB17 signal in specific cells in the embryonic, QC area of primary and lateral roots, through in situ hybridization analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Overexpression of ATHB17 in Arabidopsis enhances chlorophyll content in the leaves, while expression of a truncated ATHB17 protein in maize increases ear weight at silking3435. ATHB17 -overexpressing Arabidopsis plants are sensitive to ABA and NaCl, whereas ATHB17 knockout mutants are insensitive to ABA and NaCl at post germination stage.…”
mentioning
confidence: 99%
“…Monsanto has developed a biotechnology‐derived inbred line of maize that expresses HB17 (ATHB17), a transcription factor from A. thaliana (Hymus et al ., ; Park et al ., ). Expression of ATHB17 in hybrid maize is associated with increased ear biomass at silking compared to near‐isogenic controls (Rice et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…Case no. 3: effects of variation in grain yield on evaluation of maize hybrids with biotechnology-derived transcription factor technology Monsanto has developed a biotechnology-derived inbred line of maize that expresses HB17 (ATHB17), a transcription factor from A. thaliana (Hymus et al, 2013;Park et al, 2013). Expression of ATHB17 in hybrid maize is associated with increased ear biomass at silking compared to near-isogenic controls (Rice et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…A number of mutants in chloroplast division machinery have been identified, although they generally lead to fewer, larger plastids, which is likely to decrease the ability of a cell to optimize the spatial distribution of its photosynthetic machinery for CO 2 uptake (Chen et al , ). Although the promotion of chloroplast differentiation can be engineered (Wang et al , ), quantitatively manipulating chloroplast number and size in mesophyll cells remains a major challenge (Hymus et al , ). A simpler route to increasing the number of chloroplasts per cell (and thus S c ) may be to decrease mesophyll cell size (see previous section).…”
Section: Improving Mesophyll Conductancementioning
confidence: 99%